Examination of prefrontal cortex activity after EEG-neurofeedback stimulation in overweight cases - Al-Hiyali, Mohammed I.; Ishak, Asnor J.; Harun, Hafiz R.; Ahmad, Siti A.; Wan Sulaiman, Wan A. (Penerbit UTHM, 2019)
Food intake regulation is considered the key to weight control and overweight prevention. The brain activity in PreFrontal Cortex (PFC) plays a role in food intake behaviors. Most of the previous studies were aimed to PFC stimulation in overweight cases to modify the food intake behaviors. The EEG-neurofeedback is one of the brain stimulation techniques; therefore, this study aims to find the effect of EEG-NF stimulation on PFC function by EEG features analysis. For the purpose of analysis, the thetaβ ratio was extracted from ten healthy overweight participators in this study. All participants were divided into two groups, experimental group and control group with two phase-terms, pre and post-stimulation phase. The experiments were run using EEG-NF device. The results in this study indicate that success of EEG-Neurofeedback in PFC stimulation of overweight cases may have an influence on changing the food intake behavior.